2021
DOI: 10.1371/journal.pone.0249417
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and molecular characterization of Theileria annulata in cattle from central Khyber Pakhtunkhwa, Pakistan

Abstract: Theileria annulata is a tick-borne hemoprotozoan parasite responsible for tropical theileriosis in the bovine population, which causes substantial economic losses to the livestock sector. The present study has investigated, characterized, and shaped epidemiologic and phylogenetic profiles of T. annulata infection in the cattle population of central Khyber Pakhtunkhwa, Pakistan. A total of 600 blood samples were collected from cattle. Microscopy and PCR (18S rRNA taxonomic marker) assays were performed to detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 59 publications
3
18
1
Order By: Relevance
“…In the present study, a higher prevalence of T. annulata was recorded in female cattle from Lodhran than in males from the same District (Table 3). Our results are in accordance with the findings of Inci et al [46], Khattak et al [22] and Saeed et al [13], as they all reported a higher prevalence of T. annulata in female cattle. Saeed et al [13] reported that comparatively weak immune response and more hormonal fluctuations in females increases the incidence of theileriosis.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In the present study, a higher prevalence of T. annulata was recorded in female cattle from Lodhran than in males from the same District (Table 3). Our results are in accordance with the findings of Inci et al [46], Khattak et al [22] and Saeed et al [13], as they all reported a higher prevalence of T. annulata in female cattle. Saeed et al [13] reported that comparatively weak immune response and more hormonal fluctuations in females increases the incidence of theileriosis.…”
Section: Discussionsupporting
confidence: 94%
“…During the present study, we found that 33% of cattle from Dera Ghazi Khan and 24% from Lodhran District were infected with T. annulata ( Table 1 ). Among TBDs, bovine theileriosis has been frequently reported from various parts of Pakistan, and in previously documented studies, the prevalence of T. annulata in cattle was reported to be 33% in Peshawar and Kohat [ 19 ], 30% in Dir Upper and Chitral [ 20 ], 28% in Laki Marwat [ 21 ], 23.7% in Charsadda, Mardan and Peshawar Districts in Khyber Pakhtunkhwa [ 22 ], 21% in Layyah [ 23 ], 19% in various districts in Punjab [ 24 ] and 18.8% in three distinct zones of Khyber Pakhtunkhwa Province [ 25 ]. Similarly, the prevalence of T. annulata in cattle has been reported in other tropical and subtropical countries as well.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported in a study that infection of B. bigemina is higher among the age groups of 2-7 years in cross-bred animals (Velusamy et al, 2014). In a study carried out in Khyber-Pakhtunkhwa, Pakistan, Ullah et al (2021) reported that 23.7% of cattle were found infected with T. annulata, however, theileriosis was found to be higher in young animals as compared to adults cross-bred cattle. Another research from Pakistan reported over all T. annulata prevalence of 21%, with cross-bred cattle most susceptible (28%) followed by Sahiwal breed (19%) (Parveen et al, 2021).…”
Section: Discussionmentioning
confidence: 73%
“…[ 2 ]. The mild and subclinical infections are overlooked and animals remain carriers, but during stress conditions, the disease may flare up to a clinical state [ 6 , 7 ]. The variable clinical presentation as well as irregular clinical signs and symptoms of the disease frequently noticed by the field veterinarians could be related to genetic changes in this protistan parasite [ 8 ], but this needs to be further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The commonly used genetic markers for T . annulata identification and characterization are the small-subunit ribosomal RNA (18S rRNA) gene [ 7 , 14 , 15 ], the T . annulata merozoites surface antigen (Tams1 ) encoding gene [ 16 , 17 ], the β-tubulin gene [ 18 ], cytochrome b gene [ 19 , 20 ] and the heat shock protein 70 encoding gene (HSP70) [ 21 ].…”
Section: Introductionmentioning
confidence: 99%